A Talent for Tinkering: Developing Talents in Children From Low-Income Households Through Engineering Curriculum. (January 2018) - Robinson, Ann; Adelson, Jill L.; Kidd, Kristy A.; Cunningham, Christine M.
Guided by the theoretical framework of curriculum as a platform for talent development, this quasi-experimental field study investigated an intervention focused on engineering curriculum and curriculum based on a biography of a scientist through a comparative design implemented in low-income schools. Student outcome measures included science content achievement, engineering knowledge, and engineering engagement. The sample comprised 1, 387 Grade 1 students across 62 classrooms. Multilevel modeling was used separately for each of the three student outcome measures. The intervention resulted in an effect size of 0.28 on an out-of-level science content assessment and effect size of 0.66 for the engineering knowledge measure. Students in the intervention group reported a high level of engineering engagement. General education teachers were trained to implement the curricula through a summer institute and received coaching throughout the subsequent academic year. Evidence suggests the intervention functioned as a talent-spotting tool as teachers reported they would nominate a substantial portion of low-income and culturally diverse students for subsequent gifted and talented services. Discussion focused on the match between the needs and preferences of students from low-income households for hands-on design experiences and the curricular affordances in the engineering domain as a talent development pathway for young, poor children.